Global population divergence and admixture of the brown rat (Rattus norvegicus) - Puckett, Emily E.; Park, Jane; Combs, Matthew; Blum, Michael J.; Bryant, Juliet E.; Caccone, Adalgisa; Costa, Federico; Deinum, Eva E.; Esther, Alexandra; Himsworth, Chelsea G.; Keightley, Peter D.; Ko, Albert; et al. (Royal Society, 2016)
Native to China and Mongolia, the brown rat (Rattus norvegicus) now enjoys a worldwide distribution. While black rats and the house mouse tracked the regional development of human agricultural settlements, brown rats did not appear in Europe until the 1500s, suggesting their range expansion was a response to relatively recent increases in global trade. We inferred the global phylogeography of brown rats using 32 k SNPs, and detected 13 evolutionary clusters within five expansion routes. One cluster arose following a southward expansion into Southeast Asia. Three additional clusters arose from two independent eastward expansions: one expansion from Russia to the Aleutian Archipelago, and a second to western North America. Westward expansion resulted in the colonization of Europe from which subsequent rapid colonization of Africa, the Americas and Australasia occurred, and multiple evolutionary clusters were detected. An astonishing degree of fine-grained clustering between and within sampling sites underscored the extent to which urban heterogeneity shaped genetic structure of commensal rodents. Surprisingly, few individuals were recent migrants, suggesting that recruitment into established populations is limited. Understanding the global population structure of R. norvegicus offers novel perspectives on the forces driving the spread of zoonotic disease, and aids in development of rat eradication programmes.